Effects of Preateatment Process with Organic Acids (Averrhoa bilimbi L.) and Japansche Citroen (Citrus limonia Osbeck) Juice on Quality of Chili Powder (Capsicum frutescens) - Kusnadi, Joni; Pamulanti, Anjar (University of Brawijaya, 2019)
Preservation process like drying is needed to extend the shelf life of hot chili. However, the drying process lead much quality degradation, such as loss the nutritions. The chili need treatment with blanching and soaking with organic acid such as Japansche citroen and Averrhoa bilimbi L juice. The aim of this research is to know the effects of (Japansche citroen) and (Averrhoa bilimbi L.) juice in soaking process on quality of dried chili (Capsicum frutescens). Factorial Randomized Block Design was used in this research with 2 factor. The first factor was type of fruit juice of Japansche citroen and Averrhoa bilimbi L. The second factor was level of fruit juice concentration (5%, 10%,15%). The best result of this study is acquired from soaking with Japansce citroen with 15% of concentration. It obtains a* value 51,77±0,16, total color 174,88 ±7,78 ASTA, total phenolic content 8,51±1,11 mg GAE/g, total flavonoid content 22,86±1,24 mg QE/g, capsaicin content 1156322,498 ±95263,46 SHU, ascorbic acid content 0,6427±0,00 mg/g and antioxidant activity IC50 126,8081716 ±3,68 ppm.